Enhancement of inhibitory control in a sample of preschoolers from poor homes after cognitive training in a kindergarten setting: Cognitive and ERP evidence - Pietto, Marcos Luis (2018)
Objective: Cognitive Control (CC) is a central aspect of self-regulatory development, which can be modulated by individual differences, the quality of experiences in several developmental contexts (e.g., home, school, community), and cognitive interventions. In particular, associations between childhood poverty and cognitive and neural aspects of CC have also been documented in recent years. Less evidence is available regarding the brain areas influence by cognitive intervention in children from poor homes. In the present study, we examined the impact of a computerized, cognitive training that was implemented at a kindergarten on inhibitory control performance by cognitive and EEG methods. Methods: Children were trained weekly for 8 weeks and tested before and after the intervention using EEG recordings during a Go/NoGo task performance. Children in the intervention group (n = 24; 18 girls, mean age 5.32 ± 0.39 years) played games that tapped inhibitory control, working memory, and planning demands on a tablet, whereas those in the control group (n = 20; 7 girls, mean age 5.42 ± 0.27 years) played Internet free games with the same schedule. Results: Electrophysiological measures related to performance of inhibitory control showed improvements only in the intervention group, and no differences were found in cognitive performance. Specifically, only the intervention group showed in increase in the frontal N2-effect; that is, there was larger differentiation between the amplitude of N2-NoGo and N2-Go in the post-test stage. Conclusions: These results show: (a) that the implemented intervention modulated the neural resources related to inhibitory control processes, and (b) it is possible to implement portable neural methodologies in school settings to enhance the evaluation of cognitive training interventions by adding an EEG component.